Cultural Heritage Informatics: Past, Present, and Future - Youngman, Tyler; Modrow, Sebastian; Meth, Isaac (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2025)
This paper briefly traces the informational history and contemporary formalization of Cultural Heritage Informatics as a distinct domain within IS/LIS, motivated by recent calls for more critical, ethical, and community-oriented interrogations of IS/LIS resulting from recent debates on our professional identity. We unpack the conceptual history and disciplinary intellectual geography of “cultural heritage” and “informatics” to recount prior interpretations of the field. Next, we articulate a holistic domain-specific informatics model to guide the study of cultural heritage within IS/LIS. We conclude by articulating ethical imperatives and new directions for Cultural Heritage Informatics in research, teaching, and practice. Informatique du patrimoine culturel: Passé, présent, et futur Résumé Cet article retrace brièvement l’histoire informationnelle et la reconnaissance formelle récente de l’Informatique appliquée au Patrimoine Culturel en tant que domaine distinct au sein de l’IS/LIS, en réponse à des demandes croissantes pour une réflexion plus critique, éthique, et communautaire sur les pratiques de l’IS/LIS et l’identité du domaine. Nous analysons l’histoire conceptuelle et la géographie intellectuelle disciplinaire du patrimoine culturel et de l'informatique afin de retracer les précédentes interprétations du domaine. Ensuite, nous articulons un modèle informatique holistique, spécifique au domaine, pour guider l’étude du patrimoine culturel au sein de l’IS/LIS. Nous concluons en articulant les impératifs éthiques et les nouvelles directions de l’Informatique appliquée au Patrimoine Culturel en matière de recherche, d’enseignement, et de pratique.